Pengaruh Grit Terhadap Kreativitas Melalui Emotional Intelligence dan Work Engagement Pada Pekerja di Industri Ekonomi Kreatif: The Effect of Grit on Creativity Through Emotional Intelligence and Work Engagement in Workers in The Creative Economy Industry - Sherly Rosalina Tanoto; Gabriella Alexandra Soenyoto (Jurnal Aplikasi Bisnis dan Manajemen, 2024)
Background: The COVID-19 pandemic has had a significant impact on the global creative economy, including in Indonesia. Job losses and a decrease in the Gross Domestic Product (GDP) of this sector have prompted the government to integrate 30 million creative economy participants into the digital ecosystem by 2024. To achieve this goal, the enhancement of human resource quality (HRQ) is key. Grit, encompassing long-term passion and perseverance, has been identified as a factor influencing individual creativity.Purpose: This study examines the influence of grit on creativity through work engagement and emotional intelligence among workers in the creative economy. Design/methodology/approach: Data from 301 creative workers were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) methodFindings/Result: The research findings indicate that grit does not have a direct impact on creativity. Grit indirectly affects creativity through work engagement and emotional intelligence. Conclusion: Grit influences creativity indirectly via work engagement and emotional intelligence. Enhancing these factors is crucial for fostering creativity in individuals with high grit.Originality/value (State of the art): This study reveals the indirect effects of grit on creativity through work engagement and emotional intelligence among Indonesian creative workers. It challenges previous findings of a direct link, offering valuable insights for boosting creativity in the digital economy. Keywords: creative economy industry, creativity, emotional intelligence, grit, work engagement